Akt/AS160 Signaling Pathway Inhibition Impairs Infection by Decreasing Rab14-Controlled Sphingolipids Delivery to Chlamydial Inclusions - Capmany, Anahí; Gambarte Tudela, Julián; Alonso Bivou, Mariano; Damiani, María T. (Frontiers in Microbiology, 2019)
Chlamydia trachomatis, an obligate intracellular bacterium, intercepts different trafficking pathways of the host cell to acquire essential lipids for its survival and replication, particularly from the Golgi apparatus via a Rab14-mediated transport. Molecular mechanisms underlying how these bacteria manipulate intracellular transport are a matter of intense study. Here, we show that C. trachomatis utilizes Akt/AS160 signaling pathway to promote sphingolipids delivery to the chlamydial inclusion through Rab14-controlled vesicular transport. C. trachomatis provokes Akt phosphorylation along its entire developmental life cycle and recruits phosphorylated Akt (pAkt) to the inclusion membrane. As a consequence, Akt Substrate of 160 kDa (AS160), also known as TBC1D4, a GTPase Activating Protein (GAP) for Rab14, is phosphorylated and therefore inactivated. Phosphorylated AS160 (pAS160) loses its ability to promote GTP hydrolysis, favoring Rab14 binding to GTP. Akt inhibition by an allosteric isoform-specific Akt inhibitor (iAkt) prevents AS160 phosphorylation and reduces Rab14 recruitment to chlamydial inclusions. iAkt further impairs sphingolipids acquisition by C. trachomatis-inclusion and provokes lipid retention at the Golgi apparatus. Consequently, treatment with iAkt decreases chlamydial inclusion size, bacterial multiplication, and infectivity in a dose-dependent manner. Similar results were found in AS160-depleted cells. By electron microscopy, we observed that iAkt generates abnormal bacterial forms as those reported after sphingolipids deprivation or Rab14 silencing. Taken together, our findings indicate that targeting the Akt/AS160/Rab14 axis could constitute a novel strategy to limit chlamydial infections, mainly for those caused by antibiotic-resistant bacteria.